Correlation evaluation on circumferentially average heat transfer for supercritical carbon dioxide in non-uniform heating vertical tubes. (1st March 2019) - Fan, Y.H.; Tang, G.H.; Li, X.L.; Yang, D.L.; Wang, S.Q.
Abstract: Supercritical heat transfer mechanisms and heat transfer correlations are firstly reviewed in present paper. The heat transfer characteristics of S-CO2 in circumferentially non-uniform heated vertical upward flow are then numerically studied and the fundamental mechanisms are discussed. The abnormal heat transfer for S-CO2 is believed to be caused by the comprehensive effect of thermophysical property variations. For S-CO2 with non-uniform heating and large mass flow rate, the enhanced heat transfer is mainly related to the large specific heat in the near wall region while the deteriorated heat transfer is dominated by the thickening viscous sublayer induced by the viscosity increase. Besides, the buoyancy effect induced by the density variation is still prominent to axial velocity distribution even in the forced convection. Finally a new correlation with higher accuracy is developed for S-CO2 circumferentially average heat transfer by introducing the correction parameters of viscosity, specific heat, axial flow-acceleration and non-uniform heat flux. Highlights: Supercritical heat transfer mechanisms and correlations are comprehensively reviewed. Heat transfer of S-CO2 under non-uniform heating is numerically studied. The relation between thermophysical property variation and abnormal heat transfer is examined. An average heat transfer correlation for S-CO2 under non-uniform heating is proposed and evaluated.